Long term pregnancy outcomes of women with cancer following fertility preservation: A systematic review and meta-analysis. (February 2023) - Xu, Zilin; Ibrahim, Sameh; Burdett, Sarah; Rydzewska, Larysa; Al Wattar, Bassel H.; Davies, Melanie C
Highlights: Only 8% of women returned to use their frozen reproductive material (558/7037, 8.0%), resulting in 210 live births in total, including assisted conceptions following EC/OC/OTC and natural conceptions following OTC. The cumulative live birth rate following any fertility preservation treatment was 0.046 (95 %CI 0.029–0.066). The overall LBR was highest in women who had EC (OR 0.45, 95 %CI 0.14–0.76), followed by OTC group (OR 0.37, 95 %CI 0.22–0.53) and OC group (OR 0.31, 95 %CI 0.15–0.47). There was limited reporting on other important reproductive outcomes in this cohort including miscarriages, ectopic pregnancies and Caesarean sections rate. Abstract: Objective: As cancer survivorship increases, there is higher uptake of fertility preservation treatments among affected women. However, there is limited evidence on the subsequent use of preserved material and pregnancy outcomes in women who underwent fertility preservation (FP) before cancer treatments. We aimed to systematically review the long-term reproductive and pregnancy outcomes in this cohort of women. Patients: Women who underwent any type of the following FP treatments: embryo cryopreservation (EC), oocyte cryopreservation (OC) and ovarian tissue cryopreservation (OTC)) before any planned cancer treatment. Evidence review: We searched electronic databases (MEDLINE, Embase, Cochrane CENTRAL, and HTA) from inception until May 2021 for all observational studies that met our inclusion criteria. We extracted data on reproductive and pregnancy outcomes in duplicate and assessed the risk of bias in included studies using the ROBINS-I tool. We pooled data using a random-effects model and reported using odds ratios (OR) with 95% confidence intervals (CI). Main outcome measures: Our primary outcome was live birth rate and other important reproductive and pregnancy outcomes. Results: Of 5405 citations, we screened 103 and included 26 observational studies (n = 7061 women). Hematologic malignancy was the commonest cause for seeking FP treatments, followed by breast and gynecology cancers. Twelve studies reported on OTC (12/26, 46 %), eight included EC (8/26, 30 %), and twelve reported on OC (12/26, 46 %). The cumulative live birth rate following any FP treatment was 0.046 (95 %CI 0.029–0.066). Only 8 % of women returned to use their frozen reproductive material (558/7037, 8.0 %), resulting in 210 live births in total, including assisted conceptions following EC/OC/OTC and natural conceptions following OTC. The odds for live birth was OR 0.38 (95 %CI 0.29–0.48 I 2 83.7 %). The odds for live birth was the highest among women who had EC (OR 0.45, 95 %CI 0.14–0.76, I 2 95.1 %), followed by the OTC group (OR 0.37, 95 %CI 0.22–0.53, I 2 88.7 %) and OC group (OR 0.31, 95 %CI 0.15–0.47, I 2 78.2 %). Conclusions: Fertility preservation treatments offered good long-term reproductive outcomes for women with cancer with a high chance to achieve a live birth. Further research is needed to evaluate the long-term pregnancy and offspring outcomes in this cohort.